Applied, type and rational-using of code switching in Insecurity novel - Ambanilah, Eldalati; Hidayat, Arif; Rosalinah, Yanti (LADU: Journal of Languages and Education, 2021)
Background: Â People often used the code in their daily conversation, spoken or written language, formal or informal. When people do code switching, it can make them become bilingual.Purpose: The objective of this paper is to find out how many code switching are applied, types of code switching in dialog between the characters in Insecurity novel of Angelina Johnson included the reasons for using the code switching.Design and methods: The method used in this analysis is qualitative descriptive method with the library and internet research. This analysis focused on analyzing the types of code switching based on the theory of Poplack and reasons for using code switching based on Hoffman theory.Results: The results of analysis found the total in dialog that code switching occurs 141 data from chapter 1 to 19. Total 3 types of code switching, that most widely used is intra-sentential occurs 122 times, then inter-sentential 13 times, while tag switching occurs 6 times. And also found that only six reasons based on Hoffman theory by talking about particular topic found 47 times, quoting somebody else found 3 times, being empathic found 14 times, interjection found 6 times, repetition used for clarification found only once, while intention of clarifying found 14 times.